Manajemen Manajemen Pendidikan Karakter Siswa di Sekolah Dasar - Syukri, Makmur; Rismalinda, Rismalinda; Akbar, Hilda Marwani; Yusuf, Dodi Muhammad; Melinda, Reza (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to provide a comprehensive description of the administration of character education for students at SDN 25 Talang. This study employs a case study research design with a qualitative methodology. The data collection procedures employed include interviews, observation, and documentation. The findings of this study demonstrate that the management functions executed at SDN 25 Talang encompass (1) strategic planning for character education, which involves identifying the character values to be cultivated in the school, equipping educators and education staff, reviewing pertinent documents pertaining to the reinforcement of character education, and disseminating policies to all educational institutions, parents of students, and relevant communities. (2) The implementation of character education involves integrating pre-determined character education content into all topics, as well as incorporating it into programmed or planned activities. Implementing character education through daily activities at school, focusing on habituation and leading by example, while fostering communication and collaboration between schools and parents of kids. (3) Character education is evaluated by program evaluation, process evaluation, and evaluation of results.